Salivary Metabolomics for Oral Squamous Cell Carcinoma Detection: An Indian Perspective - Raghuram Manickam; Vijaya Nirmala Subramani (Journal of Primary Care Dentistry and Oral Health, 2026)
Abstract Salivary metabolomics has emerged as a promising noninvasive approach for the early detection of oral squamous cell carcinoma (OSCC), enabling the identification of tumor-associated metabolic alterations with potential diagnostic value. Recent systematic reviews and meta-analyses have demonstrated encouraging diagnostic accuracy for salivary metabolites, particularly lactate, choline, and phenylalanine. However, the applicability of these biomarkers to high-burden populations such as India remains inadequately explored. Emerging evidence from Indian studies has identified additional candidate salivary metabolites, suggesting that metabolic profiles may vary according to environmental exposures, tobacco and areca nut use, oral microbiota, and lifestyle factors. Despite these advances, heterogeneity in study design, saliva collection protocols, and analytical platforms, together with limited longitudinal and prognostic data, continues to impede clinical translation. Cost-effective analytical techniques and standardized saliva collection methods may facilitate the implementation of salivary metabolomics in resource-limited settings. Multicentric Indian studies integrating clinical, metabolomic, and epidemiological data are essential to validate candidate biomarkers and establish affordable, reliable screening strategies for individuals at high risk of OSCC.